EDUKASI PENTINGNYA PENERAPAN PROTOKOL KESEHATAN SEBAGAI UPAYA PENCEGAHAN PENYEBARAN COVID-19 - Halisah Suriani; Nursafiah; Rika Aswarita; Afrizal (Universitas Pahlawan Tuanku Tambusai, 2021)
This activity was carried out on Tuesday, December 1, 2020 by the Aceh UGL service Lecturer team from 10.00 WIB to 11.00 WIB in the FKP UGL Aceh Classroom, attended by 15 students. At first, observations were made to identify the implementation of health protocols, then prepared material to be delivered directly using power point presentation media, then arranged a schedule for delivering material by resource persons (devotion lecturers) regarding education about health protocols as well as conducting discussion and Q&A. the media used is the presentation of the material through LCD, videos and leaflets. Educational activities for implementing health protocols were able to increase participants’ insight and knowledge about the importance of maintaining health protocols as an effort to prevent the spread of Covid-19. This activity is felt to be very useful because the Covid-19 pandemic provides many lessons for us. Keywords: education, health protocol, prevention of the spread of covid-19